Hubungan Aktivitas Fisik Dan Stres Terhadap Kualitas Tidur Selama Pandemi Covid-19 Pada Mahasiswa Tingkat 2 Fakultas Kedokteran UPN Veteran Jakarta - Danisa Agustien Nurrachmawati; Nunuk Nugrohowati; Kristina Simanjuntak (Jurnal EnviScience (Environment Science), 2022)
Medical student activities in lectures involve many physical activities that affect student stress in lectures related to sleep quality during the Covid-19 period. The purpose of the study was to find out the relationship between stress and physical activity in sleep quality during the Covid-19 period. Coss Sectional research design, with a sample of 2nd-grade Medical Students with a total of 96 students, was taken simply random sampling. Data collection using questionnaires with physical activity was measured by the International Physical Activity Questionnaire, stress measured by perceived stress scale, and sleep quality through the Pittsburgh Sleep Quality Index. The results obtained by students with heavy physical activity experienced poor sleep quality 87.7% and moderate category stress that had poor sleep quality. 88.9% of chi-square test had no association between physical activity (p= 0,68), stress (p = 0,58), to sleep quality. Many other factors that need to be considered to get good quality sleep to stay healthy fit.Keywords: physical activity, Covid 19, sleep quality, stress